The Use of Virtual Reality Technologies in the Treatment of Duchenne Muscular Dystrophy: Systematic Review. - Baeza-Barragán, María Rosa; Labajos-Manzanares, María Teresa; Ruiz Vergara, Carmen; Casuso Holgado, María Jesús; Martín-Valero, Rocío (JMIR, 2020)
Duchenne muscular dystrophy is a serious and progressive disease affecting one in 3500-6000 live male births. The use of new virtual reality technologies has revolutionized the world of youth rehabilitation. Objective: We performed a systematic review to study the effectiveness of the use of virtual reality systems applied in the rehabilitation of the upper limbs of individuals with Duchenne muscular dystrophy. Methods: Between June 2018 and September 2019, we carried out a series of searches in 5 scientific databases. Two evaluators independently conducted the searches following the PRISMA recommendations for systematic reviews for articles. Article quality was determined using the PEDro scale. A total of 7 clinical trials were included in the final review. These studies used new technologies as tools for physiotherapeutic rehabilitation of the upper limbs of patients with Duchenne muscular dystrophy. Collectively, the studies showed improvement in functionality, quality of life, and motivation with the use of virtual reality technologies in the rehabilitation of upper limbs of individuals with Duchenne muscular dystrophy. Conclusions: The treatment of neuromuscular diseases has changed in recent years, from palliative symptom management to preventive methods for capacity building. The use of virtual reality is beginning to be necessary in the treatment of progressive diseases involving movement difficulties, as it provides freedom and facilitates the improvement of results in capacity training. Given that new technologies are increasingly accessible, rehabilitation and physiotherapy programs can use these technologies more frequently, and virtual reality environments can be used to improve task performance, which is essential for people with disabilities. Ultimately, virtual reality can be a great tool for physiotherapy and can be used for Duchenne muscular dystrophy rehabilitation programs to improve patient performance during training.
Keywords: Distrofia muscular; Duchenne, Distrofia muscular de; Pacientes - Rehabilitación; Fisioterapia - Innovaciones tecnológicas; Realidad virtual en medicina; Duchenne muscular dystrophy; Virtual reality; Upper limb; Physical therapy; Muscular dystrophy; Mutation; Muscle; Degeneration